2011
DOI: 10.1080/09658211.2010.530271
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of familiarity and recollection rejection to recognition: Evidence from the time course of false recognition for semantic and conjunction lures

Abstract: It has been suggested that both familiarity and recollection contribute to the recognition decision process. In this paper, we leverage the form of false alarm rate functions-in which false-alarm rates describe an inverted U-shaped function as the time between study and test increases-to assess how these processes support retention of semantic and surface form information from previously studied words. We directly compare the maxima of these functions for lures that are semantically related and lures that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 63 publications
(112 reference statements)
1
31
1
Order By: Relevance
“…As mentioned in the introduction, conjunction items are lures that are similar or related to studied faces and may be falsely recognized as old on the basis of familiarity [11,12,14]. The analyses showed that the waveform differences between conjunction and new faces distributed over frontal, central, and parietal cortical regions, and the occurrence of such differences were relatively later (∼900 ms after stimulus onset) compared with those between the old and the new faces (roughly 300 ms).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As mentioned in the introduction, conjunction items are lures that are similar or related to studied faces and may be falsely recognized as old on the basis of familiarity [11,12,14]. The analyses showed that the waveform differences between conjunction and new faces distributed over frontal, central, and parietal cortical regions, and the occurrence of such differences were relatively later (∼900 ms after stimulus onset) compared with those between the old and the new faces (roughly 300 ms).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, the discriminations of the stimuli that are composed of a mixture of features from previous actually presented items have received renewed interest with the use of the feature-conjunction paradigm [10][11][12]. For instance, participants might study the items such as keyboard and foxhole, and then in a recognition test, they are required to discriminate the compound words, such as keyhole (both parts old but recombined) or blackboard (partly old), and the entirely new words, from the old words that have been encountered in the previous study list.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing memory for the correct proposition might also help readers reject the lures by process of elimination (the phenomenon of recollection rejection; Brainerd, Reyna, & Estrada, 2006; Matzen, Taylor, & Benjamin, 2011), but it should not do so exclusively for particular types of probes. That is, superior memory for the true proposition should help reject both the alternative lure ( French ) and the unmentioned lure ( Portuguese ).…”
Section: Methodsmentioning
confidence: 99%
“…Note that the peak of the curve shifts further to the left as the density of the context representation increases (Matzen, Taylor, & Benjamin, 2009). This finding indicates that, with greater representational density, a lower probability of recovering an individual feature is sufficient to support disambiguation of the context.…”
Section: The Representational Model Of Memory Judgments: Implementatimentioning
confidence: 99%